Treatment of coronary lesions with a novel crystalline sirolimus-coated balloon - Madanchi, Mehdi; Attinger-Toller, Adrian; Gjergjizi, Varis; Majcen, Irena; Cioffi, Giacomo M.; Epper, Angelika; Gnan, Eleonora; Koch, Tanja; Zhi, Yuan; Cuculi, Florim; Bossard, Matthias (Frontiers in Cardiovascular Medicine, 2024)
Background: There is mounting data supporting the use of drug-coated balloons (DCB) not only for treatment of in-stent restenosis (ISR), but also in native coronary artery disease. So far, paclitaxel-coated balloons represented the mainstay DCBs. The SeQuent ® crystalline sirolimuscoated balloon (SCB) (B.Braun Medical Inc, Germany) represents a novel DCB, which allows a sustained release of the limus-drug. We evaluated its performance in an all-comer cohort, including complex coronary lesions.Methods: Consecutive patients treated with the SeQuent ® SCB were analyzed from the prospective SIROOP registry (NCT04988685). We assessed clinical outcomes, including major adverse cardiovascular events (MACE), target lesion revascularization (TLR), target vessel myocardial infarction (TV-MI) and cardiovascular death. Angiograms and outcomes were independently adjudicated.Results: From March 2021 to March 2023, we enrolled 126 patients and lesions, of which 100 (79%) treated using a "DCB-only" strategy and 26 (21%) with a hybrid approach (DES+DCB).The mean age was 68±10years, 48 (38%) patients had an acute coronary syndrome. Regarding lesion characteristics, ISR was treated in 27 (21%), 11 (9%) underwent CTO-PCI and 59 (47%) of the vessels were moderate to severe calcified. Procedural success rate was 100%. At a median follow-up time of 12.7 (IQR 12; 14.2) months, MACE occurred in 5 patients (4.3%). No acute vessel closure was observed.Conclusions: Our data indicates promising outcomes following treatment with this novel crystalline SCB in an all-comer cohort with complex coronary lesions. These results require further investigation with randomized trials.